LEAN LIBRARY COMMUNICATION : MIND THE CUSTOMER - Huizing, Bert (European Scientific Journal, ESJ, 2014)
Academic libraries have been discovering communication as an important organizational process. Communication seems to be a relevant and important factor to connect with library customers, and - as a result - to involve and to captivate library customers. However, academic libraries tend to fail in organizing communication processes in a customer oriented way. This is most visible in the use of a wide range of (technology enhanced) communication channels like – for example - social media. This behavior is risky because of probably wrong choices, the waste of valuable resources and forget what library customers want. In this research is investigated how academic libraries should organize communication processes in a customer oriented way. The research has been carried out by a literature study about communication processes, communications channels and effective communication. In the empirical part a group of University students were asked to respond to a survey about their communication preferences with an academic library. Results show that students prefer to communicate face-toface, e-mail, or simply check the library’s website.